2015
DOI: 10.1089/gtmb.2014.0271
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Insertion/Deletion Polymorphism in the Promoter Region of the NFKB1 Gene Increases the Risk of Papillary Thyroid Carcinoma

Abstract: This study aimed to assess whether an insertion/deletion polymorphic variation rs28362491 in the NFKB1 promoter region was related to the risk of papillary thyroid carcinoma (PTC). Genomic DNA was extracted from the peripheral venous blood of 352 patients with PTC and 459 controls. The NFKB1 rs28362491 polymorphism was genotyped by using a polymerase chain reaction assay. We found that the frequency of the heterozygous genotype ATTG1/ATTG2 was significantly higher in the cases compared to the controls (odds ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 56 publications
(69 reference statements)
0
9
0
Order By: Relevance
“…Several studies suggested genetic variations of NF‐κB signaling confers increase risk for multiple cancers including NPC (Suzairi, Aizat, Aminudin, Nurfatimah, & Ankathil, ; Wang et al, ; Zhang et al, ; Zhou et al, ). Recently, whole‐exome sequencing studies from different groups consistently documented loss of function (LOF) mutations on multiple negative regulators of the NF‐κB pathway occur in nearly half of somatic NPC, including NFKBIA (Li, Chung, et al, ; Zhang, MacIsaac, et al, ; Zheng et al, ), CYLD (Li, Chung, et al, ; Zhang, MacIsaac, et al, ; Zheng et al, ), TRAF3 (Li, Chung, et al,; Zhang, MacIsaac, et al, ; Zheng et al, ), and TNFAIP3 (Zheng et al, ), NLRC5 (Li, Chung, et al, ; Zhang, MacIsaac, et al, ).…”
Section: High Prevalence Of Genetic Variants Of Nf‐κb Pathway Componementioning
confidence: 99%
“…Several studies suggested genetic variations of NF‐κB signaling confers increase risk for multiple cancers including NPC (Suzairi, Aizat, Aminudin, Nurfatimah, & Ankathil, ; Wang et al, ; Zhang et al, ; Zhou et al, ). Recently, whole‐exome sequencing studies from different groups consistently documented loss of function (LOF) mutations on multiple negative regulators of the NF‐κB pathway occur in nearly half of somatic NPC, including NFKBIA (Li, Chung, et al, ; Zhang, MacIsaac, et al, ; Zheng et al, ), CYLD (Li, Chung, et al, ; Zhang, MacIsaac, et al, ; Zheng et al, ), TRAF3 (Li, Chung, et al,; Zhang, MacIsaac, et al, ; Zheng et al, ), and TNFAIP3 (Zheng et al, ), NLRC5 (Li, Chung, et al, ; Zhang, MacIsaac, et al, ).…”
Section: High Prevalence Of Genetic Variants Of Nf‐κb Pathway Componementioning
confidence: 99%
“… 8 Studies have shown the association of NF-κB1 gene with thyroid cancer, oral squamous cell carcinoma, and colorectal cancer. 9 11 However, there is little research on the association of NF-κB1 and gliomas. According to our previous study, NF-κB1 was highly expressed in gliomas.…”
Section: Introductionmentioning
confidence: 99%
“…Prostate cancer (Zhang et al 2009, Kopp et al 2013, Cui et al 2015, Han et al 2015 rs28362491, rs2233406, rs3138053, rs28362491 Susceptibility 24:7 the rs28362491 insertion/deletion polymorphism in NFKB1 and has identified this polymorphism as a susceptibility factor for PTC (Wang et al 2015). We hypothesize that NF-κB-related genetic variants could represent important risk factors in development or clinical progression of NMTC and could improve our understanding of the mechanisms responsible for the effects of NF-κB on RAI responsiveness.…”
Section: Susceptibilitymentioning
confidence: 89%
“…References NF-κB polymorphisms Associated with Thyroid cancer (Wang et al 2015) rs28362491 Susceptibility Breast cancer (Wang et al 2014, Eskandari-Nasab et al 2016 rs28362491, rs2233406 Susceptibility (Jamshidi et al 2015) rs5996080, rs7973914, rs17243893, rs57890595…”
Section: Type Of Endocrine-related Malignancymentioning
confidence: 99%